Human Capital Risk, Contract Enforcement, and the Macroeconomy - Krebs, Tom; Kuhn, Moritz; Wright, Mark L. J. (American Economic Review, 2015)
We use microdata to show that young households with children are underinsured against the risk that an adult member of the household dies. This empirical finding can be explained by a macroeconomic model with human capital risk, age-dependent returns to human capital investment, and endogenous borrowing constraints due to limited contract enforcement. When calibrated, the model quantitatively accounts for the observed life-cycle variation in life insurance holdings, financial wealth, earnings, and consumption inequality. The model also predicts that reforms making consumer bankruptcy more costly will substantially increase the volume of both credit and insurance. (JEL D14, D91, G22, J13, J24)